Developing a micro tasking online crowdsourcing platform for handworkers - Muhammad Akram Mat Lazim; Farah Nadia Azman (Institute of Advanced Engineering and Science, 2026)
Online crowdsourcing has emerged as economic solutions for digitally literate modern society. The use of non-standard employees is what defines the gig economy, in which the hired crowds execute short-term, on-demand micro job assignments for a range of people or companies. Despite the existence of several local crowdsourcing app in the market, there is lack of study on the interaction model of a micro tasking online crowdsourcing platform for handworkers such as plumbing and piping, furniture and household items repairs, installation, electrical repairs, house modelling, carpeting and more. Hence, a prototype of virtual middleman system for handworker crowdsourcing is developed. The technical requirements and design principles of a web-based handworker crowdsourcing system are identified. Evaluation results of functionality, usability, interface and compatibility testing are presented. Essentially, this study contributes to the body of literature by granting a transferable technical requirements and economical potential of virtual middleman system for handworker crowdsourcing. However, the system was tested in a controlled environment with a limited user base, which may not fully represent real-world usage scenarios. Hence, subsequent study should incorporate performance indicators such as task completion rate, latency, or long-term user engagement.